RESEARCH FRONTIERS AND TRENDS IN YOUTH EMPOWERMENT: A BIBLIOMETRIC ANALYSIS FROM YEAR 2015-2025 - Ali, Jurainah; Adam, Ainul Azreen (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Youth empowerment is widely discussed across health, education, community development, and policy research. However, rapid growth and varied terminology make it difficult to obtain an integrated picture of how the field has progressed and where contemporary research efforts are focused. This bibliometric analysis maps publication trends, influential articles, leading countries, major keywords, and international collaboration patterns in the Scopus-indexed literature on empowerment among youth. Using Scopus’s advanced search, 1,041 records were retrieved. Data was cleaned and harmonized in OpenRefine to improve consistency of metadata (e.g., author keywords and country names). Scopus Analyzer was used to generate descriptive statistics and trend graphs, while VOSviewer was applied to visualize keyword co-occurrence as well as country co-authorship networks. The results demonstrate a substantial rise in annual publication output, rising from 29 publications in 2015 to 109 publications in 2025, with more rapid expansion after 2020. The top 10 most cited articles (published between 2015 and 2020) received between 71 and 95 citations, suggesting that a small set of applied and methodologically robust studies attracts substantial attention. The United States is on top with 274 publications, followed by the United Kingdom with 75 and Australia with 47, with some Asian and African countries also making significant contributions. The output of the country is concentrated in a few research centers. A total of 1,356 distinct keywords were generated through the process of keyword mapping. A threshold of five instances was used for 102 retained terms, with the centrally placed terms “empowerment,” “adolescent,” and “youth” associated with topics or challenges such as economic empowerment, mental health, and participatory modalities. At the same time, the co-authorship research revealed 103 countries, and 43 of them fulfilled the minimum-document condition, and the United States was a significant center of cooperation (Total Link Strength = 132). Overall, the findings contribute to more efficient agenda-setting.